INCREASING THE UNIFORMITY OF COTT?NVARIES ANDIJAN35 SOWN IN THEANDIJAN REGUON - ?gamov ?husanboy , Kimsanov Ibroximjon Xayitmuratovich , Rasulov Soyibjon Tolibjonovich , Abdurahimova Anora Rustamboevna, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the article, pure seeds of 2017-2019 year Andijan-35 cotton variety were collected from isolated families in the extreme conditions of Andijan region. As a result, three thousand five hundred and fifty individual samples, 205 kg of super elite, 8060 kg of elite and 41.8 tons of 1st reproduction seeds were prepared from the seedlings. It is also reported that as a result of three field inspections, the fertility of families has reached 100 percent.